Preparation and in-vitro Evaluation of Zolmitriptan Nasal SemiSolid Formulations - عثمان محمد; بركات هيا (Latakia University Journal -Medical Sciences Series, 2020)
This study aims to prepare SemiSolid nasal Formulations, of Zolmitriptan "anti-migraine" to investigate their physiochemical properties and in-vitro release studies, in order to improve their Pharmacokinetics and therapeutic properties, this study has started by using a pure Zolmitriptan Ultraviolet absorption (UV Spectrophotometery), Fourier Transformation Infra Red (FTIR), Differential Scanning Calorimetry (DSC), and X-Ray Diffraction (XRD) of the drug and the excipients looking for possible interactions between them. Zolmitriptan gels, creams (Emulgel), and ointments were prepared. The experiments showed that the formulation of Zolmitriptan gels based on carbopol 940 were the best among the formulas, in terms of rapid in-vitro releases of the drug, by using an (Enhancer cell).